CONNECTING ROD FAILURE ANALYSIS UNDER MAXIMUM LOADING - Suryadi, Dedi (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2019)
Motorcycle is one of the public transportation consisting of several components. One of the main components is connecting rod, that is a connector part between the piston and crankshaft. Connecting rod is often getting damage, such as bent or broken. The damage is as the result of the continuously working connecting rod that caused a fatigue on components. Therefore, strength analysis is needed to be conducted to determine the cause of the damage on the connecting rod. The application of force on the mechanism crank must be considered especially in the analytical calculations and simulations. The object of this research is the connecting rod of motorcycle using AISI 1070 material. The finite elements model is applied on the model by using ANSYS workbench 14.0 software. The boundary conditions are also applied on the big end part is fixed suport, while at the small end is subjected to loads due to the dynamic motion of the system. As the results, maximum stress and safety factor are obtained. The maximum stress is 164.7 MPa and smaller end part with safety factor of 3.01. According to the result, the connecting rod is safe